A trial separation : Australia and the decolonisation of Papua New Guinea - Denoon, Donald (ANU E Press, 2012)
When it came in September 1975, Papua New Guinea's independence was marked by both anxiety and elation. In the euphoric aftermath, decolonisation was declared a triumph and immediate events seemed to justify that confidence. By the 1990s, however, events had taken a turn for the worse and there were doubts about the capacity of PNG to function. This history presents the full story of the 'trial separation' of Australia and Papua New Guinea, concluding that -- given the intertwined history, geography and economies of the two neighbours -- the decolonisation project of 'independence' is still a work in progress.